Nutritional Value and Potential Chemical Food Safety Hazards of Selected Traditional and Conventional Pork Hams from Poland. (20th September 2017) - Halagarda, Michał; Kędzior, Władysław; Pyrzyńska, Ewa
Abstract : Consumers no longer look for food characterized only by health safety and proper nutritional value. As a result, an increased interest in traditional and regional food can be observed. The aim of this paper is to analyze the results of a comparative analysis of three types of hams: traditional products registered on the List of Traditional Products of the Polish Ministry of Agriculture and Rural Development, then products whose names, retail prices, appearance, and manufacturer's description suggest traditional methods of production, and finally conventional hams. The results show that traditional hams are characterized by the highest nutritional value among the analyzed groups of products. They have the lowest water and a high protein content. In addition, traditional hams are distinguished by a low concentration of sodium chloride and no addition of phosphates. The residues of nitrites and nitrates indicate their moderate use in manufacturing processes.